Foreign language anxiety in Spanish as a Foreign Language and language achievement in Higher Education - Mercedes Rabadán (Revista de Estudios e Investigación en Psicología y Educación, 2018)
Language anxiety is recognized as one of the affective elements with greater influence on the learning of foreign languages. However, few studies have been conducted on anxiety in the context of Spanish as a Foreign Language (SFL), and there is hardly research with Portuguese learners in higher education. This article explores the role of language anxiety as a predictor of academic performance in Portuguese university students. We conducted a cross-sectional correlational study assessing a final sample of 249 participants. Language anxiety was assessed using the Foreign Language Classroom Anxiety Scale (FLCAS) and academic performance was evaluated using the final grade obtained in the discipline of Spanish as a foreign language. Results showed that higher scores in communication apprehension, anxiety during the evaluation and fear of a negative evaluation were associated with poorer academic performance. Regression model showed that fear of a negative evaluation was the most important predictor of grade. Anxiety-free environments facilitate the acquisition and learning of SFL.